UV glue for bonding sunglasses lens

By combining polyurethane acrylate oligomer and a multifunctional thiol mercaptosilane coupling agent, a UV adhesive without primer was developed, which solved the problem of insufficient adhesion of TAC/PC lenses, and achieved efficient and stable bonding effect and good moisture and heat resistance.

CN119529228APending Publication Date: 2025-02-28SUZHOU HAOBANG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852255.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing UV adhesives lack adhesion when bonding TAC and PC lenses, and require chemical primer for surface treatment. The process is complex, costly and unstable.

Method used

A polyurethane acrylate oligomer is used to combine with a polyfunctional thiol mercaptosilane coupling agent, and through vacuum mixing and the use of a photoinitiator, a UV adhesive without a primer is formed.

Benefits of technology

It achieves good bonding strength of TAC/PC lenses without surface treatment, has excellent moisture and heat resistance, and maintains a high bonding strength after boiling experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190887400000011
    Figure BDA0005190887400000011
  • Figure BDA0005190887400000021
    Figure BDA0005190887400000021
  • Figure BDA0005190887400000051
    Figure BDA0005190887400000051
Patent Text Reader

Abstract

The invention discloses a UV adhesive for bonding sunglass lenses. The composition is prepared from the following components in parts by weight: 100 parts of polyurethane acrylate oligomer, 20 to 60 parts of acrylate monomer, 0.5 to 5 parts of polyfunctional group thiol (sulfydryl) silane coupling agent and 0.5 to 5 parts of photoinitiator. The adhesive disclosed by the invention has excellent bonding strength on a TAC (cellulose triacetate) film, and can be used for bonding multiple layers of laminated films of sunglasses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to UV adhesive for bonding sunglass lenses, and belongs to the technical field of adhesives. Background Art

[0002] Sunglasses currently mostly use resin lenses to replace heavy and fragile glass lenses. In order to achieve a clear field of vision, avoid glare, prevent surface scratches, and be strong and lightweight, it is often necessary to bond multiple layers of lenses (PVA / TAC / PC) with different materials and functions together. Among them, UV glue is often used to bond TAC (triacetyl cellulose) and PC. PC is relatively easy to bond, but the polyurethane acrylate resin used in most UV glues has no adhesion to TAC, which is a technical problem that has plagued the industry for many years. At present, the bonding of TAC / PC often requires the use of chemical primers to treat the surface of TAC before a relatively satisfactory adhesion can be obtained. Chemical primers generally contain a large amount of organic solvents, have a strong odor, are flammable and explosive, are not friendly to the closed use environment of the factory, have complex processes, high costs, and the treatment effect is not stable enough. The market is in urgent need of a UV glue for TAC / PC bonding that does not require a primer. Summary of the invention

[0003] The purpose of the present invention is to provide a UV adhesive for bonding sunglass lenses (TAC / PC).

[0004] The technical solution to achieve the purpose of the present invention is:

[0005] In the first aspect, the present invention provides a polyurethane acrylate oligomer, the structure of which is as follows:

[0006]

[0007] Here, R1 is H or methyl, and n is an integer from 10 to 2000.

[0008] In a second aspect, the present invention provides a method for synthesizing a polyurethane acrylate oligomer, comprising: adding 430 g of bisphenol A bis(2-hydroxypropyl) ether, 650-700 g of (methyl) acrylate isobornyl and 0.4-0.5 g of p-hydroxyanisole (MeHQ) into a three-necked flask equipped with a condenser, mixing them evenly in vacuum and introducing dry nitrogen, adding 420 g of toluene-2,4-diisocyanate (TDI) and 0.3-0.5 g of dibutyltin dilaurate catalyst, reacting at 80° C. for 1 hour, continuously adding 1200 g of polytetrahydrofuran diol, reacting at 80° C. for 30 minutes, and finally adding 240-269 g of hydroxypropyl acrylate or hydroxypropyl methacrylate, and reacting at 80° C. for 1 hour to obtain a polyurethane acrylate oligomer.

[0009] In a third aspect, the present invention provides a UV adhesive composition for bonding sunglass lenses, comprising, by weight percentage: 100 parts of the polyurethane acrylate oligomer described in the first aspect, 20 to 60 parts of acrylate monomers, 0.5 to 5 parts of multifunctional thiol (mercapto) silane coupling agents, and 0.5 to 5 parts of photoinitiators.

[0010] Furthermore, the multifunctional thiol (mercapto) silane coupling agent has an adhesion promoting effect, which is of great help in improving the adhesion of the TAC film, and has the following structure:

[0011]

[0012] Wherein, R represents a methyl group or a methoxy group, and n is an integer of 0 to 100.

[0013] Furthermore, the multifunctional thiol (mercapto) silane coupling agent is synthesized by hydrolysis of mercaptopropylmethyldimethoxysilane coupling agent and / or mercaptopropyltrimethoxysilane coupling agent in the presence of a catalyst;

[0014] Specifically, the catalyst is selected from any one or more of inorganic acid, organic acid, organotin compound, cation exchange resin, titanate compound, α-silane coupling agent, Lewis acid or Lewis base compound, preferably any one or more of inorganic acid, organic acid and organotin compound; the weight ratio of mercaptopropylmethyldimethoxysilane coupling agent and / or mercaptopropyltrimethoxysilane coupling agent to the catalyst is 100:0.05-2;

[0015] More specifically, the inorganic acid and organic acid are hydrochloric acid, sulfuric acid, phosphoric acid, methanesulfonic acid, trifluoromethanesulfonic acid, toluenesulfonic acid, etc.;

[0016] More specifically, the organotin compound is dibutyltin dibutyl ketoxime silicon, dibutyltin diacetylacetonate, dibutyltin diacetylacetate, dibutyltin dilaurate, dibutyltin bistriethoxysilicate, dioctyltin bistriethoxysilicate, and a tetravalent tin compound which is a reaction product of diketoxime tin oxide and a silicate compound.

[0017] Further, the acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), 2-phenoxyethyl acrylate (PHEA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably isobornyl acrylate, 2-phenoxyethyl acrylate (PHEA), tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).

[0018] Further, the photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) or α-aminoalkylphenone. One or a mixture of several of them.

[0019] Further, based on water resistance considerations, the adhesive may also include a silane coupling agent, including but not limited to: one or more of γ-methacryloxypropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, anilinemethyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-ureapropyltriethoxysilane.

[0020] Furthermore, the adhesive may also contain free radical inhibitors, antioxidants, UV inhibitors, flame retardants, diluents, adhesion promoters, dyes, pigments, color change agents, defoaming agents, leveling agents, etc., which are well known to those skilled in the art and will not be elaborated here.

[0021] In a fourth aspect, the present invention provides a UV adhesive for bonding sunglass lenses prepared from the composition described in the third aspect.

[0022] Compared with the prior art, the advantages of the present invention are:

[0023] (1) The UV adhesive of the present invention can obtain good bonding strength without surface treatment of TAC.

[0024] (2) The UV adhesive of the present invention has excellent moisture and heat resistance and still maintains good bonding strength after the water boiling test. DETAILED DESCRIPTION

[0025] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0028] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0029] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.

[0030] Synthesis Example of Polyurethane Acrylate Oligomer

[0031] [PU-01] Add 430g of bisphenol A bis(2-hydroxypropyl) ether, 700g of isobornyl acrylate, and 0.5g of p-hydroxyanisole (MeHQ) into a three-necked flask equipped with a condenser, mix well in vacuum, and then introduce dry nitrogen. Add 420g of toluene-2,4-diisocyanate (TDI) and 0.3g of dibutyltin dilaurate catalyst, and react at 80°C for 1 hour. Continue to add 1200g of polytetrahydrofuran diol and react at 80°C for 30 minutes. Finally, add 240g of hydroxypropyl acrylate and react at 80°C for 1 hour to obtain a polyurethane acrylate oligomer, named PU-01. The viscosity is 254000mPas (25°C, Brookfield viscometer, 52Z, 5rpm).

[0032] [PU-02] Add 430g of bisphenol A bis(2-hydroxypropyl) ether, 650g of isobornyl methacrylate, and 0.4g of p-hydroxyanisole (MeHQ) into a three-necked flask equipped with a condenser, mix well in vacuum, and then introduce dry nitrogen. Add 420g of toluene-2,4-diisocyanate (TDI) and 0.5g of dibutyltin dilaurate catalyst, and react at 80°C for 1 hour. Continue to add 1200g of polytetrahydrofuran diol and react at 80°C for 30 minutes. Finally, add 269g of hydroxypropyl methacrylate and react at 80°C for 1 hour to obtain a polyurethane acrylate oligomer, named PU-02. The viscosity is 267000mPas (25°C, Brookfield viscometer, 52Z, 5rpm).

[0033] The following is an example of the hydrolysis synthesis of a multifunctional thiol silane coupling agent.

[0034] [Mercaptosilane coupling agent-1] In a three-necked glass flask with a reflux condenser, add 100 g of mercaptopropylmethyldimethoxysilane coupling agent (commercially available chemical reagent), 5 g of deionized water, 50 g of ethanol, and 0.5 g of dibutyltin bistriethoxysilicate. Stir and heat to 60°C for 5 h. Rotary evaporate to remove unreacted water, ethanol solvent and generated methanol to obtain a multifunctional mercaptosilane coupling agent-1 with a viscosity of 5.8 mPas.

[0035] [Mercaptosilane coupling agent-2] In a three-necked glass flask with a reflux condenser, add 100g of mercaptopropylmethyldimethoxysilane coupling agent, 15g of deionized water, 50g of ethanol, and 0.1g of trifluoromethanesulfonic acid. Stir and heat to 60°C for 5h, then cool to room temperature. Add excess sodium carbonate to neutralize the residual trifluoromethanesulfonic acid, filter out the solid sodium carbonate by sedimentation, and remove the ethanol solvent and the generated methanol by rotary evaporation to obtain a multifunctional thiol silane coupling agent-2 with a viscosity of 45mPas.

[0036] [Example 1] - [Example 4] The formula is shown in Table 1, and the preparation process is the same. Add the polyurethane acrylate oligomer, acrylate monomer, polythiol silane coupling agent, photoinitiator and coupling agent to a planetary mixer, and stir and mix them evenly in a vacuum in the dark.

[0037] [Comparative Example 1] - [Comparative Example 3] The formulas are shown in Table 1, and the preparation processes are the same.

[0038] The test results of various embodiments and comparative examples are shown in Table 1.

[0039] Table 1

[0040]

[0041] Note: Baojun Chemical 2900 is a polyurethane acrylate oligomer with good bonding strength to PET film; PHEA is 2-phenoxyethyl acrylate; IBOA is isobornyl acrylate; ACMO is acryloylmorpholine; THFA is tetrahydrofuran acrylate; KBM403 is Shin-Etsu γ-glycidyloxypropyl trimethoxysilane; KBM5103 is Shin-Etsu 3-(acryloyloxy)propyl trimethoxysilane; Darocure 1173 is a photoinitiator; TPO-L is ethyl 2,4,6-trimethylbenzoylphenylphosphonate, a liquid photoinitiator. All are commercially available chemical reagents.

[0042] Preparation of 180° peel strength test piece: 80μm thick TAC and PC film were wiped with alcohol to remove surface oil and dust. The adhesive coating was controlled at about 50μm, and UV curing was performed after glue bonding. The UV irradiation dose was 1000mJ / cm on both sides. 2, place at room temperature for 30 minutes to test the peel strength. The test method is in accordance with GB / T 2792-2014.

[0043] Comparing the results of Examples 1 to 4 in Table 1, it can be found that the polyurethane acrylate oligomer of the present invention, in combination with a multifunctional thiol silane coupling agent and various acrylate monomers and initiators, has very good peel strength for TAC / PC, and excellent water resistance. The peel strength decreases very little after boiling for 2 hours. However, since no multifunctional thiol silane coupling agent is added to Comparative Example 1, its peel strength is only about 1 / 3 of that of Example 4, and it decreases to 43% of the original strength after boiling. Compared with Example 3, Comparative Example 2 uses mercaptopropylmethyldimethoxysilane coupling agent to replace the multifunctional thiol coupling agent synthesized by the present invention, and the peel strength decreases from 4218g / 25cm to 2759g / 25cm, and it even decreases to 21% of the original strength after boiling. Comparative Example 3 uses a commercially available polyurethane acrylate oligomer with good adhesion to PET film. Although it also has good peel strength for TAC / PC, it also decreases significantly after boiling, only 34% of that before boiling, which is far from meeting the water resistance requirements of sunglass lenses.

[0044] The above-mentioned implementation cases are only preferred implementation cases in the present invention, but the implementation methods of the present invention are not limited to the above-mentioned implementation cases. For example, various forms of combinations of the schemes in the embodiments, any other changes, modifications, substitutions, and combinations made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are within the protection scope of the present invention.

Claims

1. A polyurethane acrylate oligomer, characterized in that: Its structure is as follows: Here, R1 is H or methyl, and n is an integer from 10 to 2000.

2. A method for synthesizing the polyurethane acrylate oligomer according to claim 1, characterized in that: include: 430 g of bisphenol A bis(2-hydroxypropyl) ether, 650-700 g of (methyl) acrylate isobornyl and 0.4-0.5 g of p-hydroxyanisole are added into a three-necked flask equipped with a condenser, and dry nitrogen is introduced after being evenly mixed in vacuum, 420 g of toluene-2,4-diisocyanate and 0.3-0.5 g of dibutyltin dilaurate catalyst are added, and the mixture is reacted at 80° C. for 1 hour, 1200 g of polytetrahydrofuran diol is continuously added, and the mixture is reacted at 80° C. for 30 minutes, and finally 240-269 g of hydroxypropyl acrylate or hydroxypropyl methacrylate is added, and the mixture is reacted at 80° C. for 1 hour to obtain a polyurethane acrylate oligomer.

3. A UV adhesive composition for bonding sunglass lenses, characterized in that: Calculated by weight percentage, it comprises: 100 parts of the polyurethane acrylate oligomer as claimed in claim 1, 20 to 60 parts of acrylate monomers, 0.5 to 5 parts of multifunctional thiol (mercapto) silane coupling agents, and 0.5 to 5 parts of photoinitiators.

4. The composition according to claim 3, characterized in that The multifunctional thiol (mercapto) silane coupling agent has the following structure: Wherein, R represents a methyl group or a methoxy group, and n is an integer of 0 to 100.

5. The composition according to claim 3, characterized in that The multifunctional thiol (mercapto) silane coupling agent is synthesized by hydrolysis of mercaptopropylmethyldimethoxysilane coupling agent and / or mercaptopropyltrimethoxysilane coupling agent in the presence of a catalyst; Specifically, the catalyst is selected from any one or more of inorganic acid, organic acid, organotin compound, cation exchange resin, titanate compound, α-silane coupling agent, Lewis acid or Lewis base compound, preferably any one or more of inorganic acid, organic acid and organotin compound; the weight ratio of mercaptopropylmethyldimethoxysilane coupling agent and / or mercaptopropyltrimethoxysilane coupling agent to the catalyst is 100:0.05-2; More specifically, the inorganic acid and organic acid are hydrochloric acid, sulfuric acid, phosphoric acid, methanesulfonic acid, trifluoromethanesulfonic acid, toluenesulfonic acid, etc.; More specifically, the organotin compound is dibutyltin dibutyl ketoxime silicon, dibutyltin diacetylacetonate, dibutyltin diacetylacetate, dibutyltin dilaurate, dibutyltin bistriethoxysilicate, dioctyltin bistriethoxysilicate, and a tetravalent tin compound which is a reaction product of diketoxime tin oxide and a silicate compound.

6. The composition according to claim 3, characterized in that The acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), 2-phenoxyethyl acrylate (PHEA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably any one or two of isobornyl acrylate, 2-phenoxyethyl acrylate (PHEA), tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).

7. The composition according to claim 3, characterized in that The photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) or α-aminoalkylphenone, or a mixture of several thereof.

8. The composition according to claim 3, characterized in that The composition further comprises a silane coupling agent, which is selected from one or more of γ-methacryloxypropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, anilinemethyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-ureapropyltriethoxysilane.

9. The composition according to claim 3, characterized in that The composition further comprises a free radical inhibitor, an antioxidant, an anti-ultraviolet agent, a flame retardant, a diluent, an adhesion promoter, a dye, a pigment, a color-changing agent, a defoaming agent, and a leveling agent.

10. A UV adhesive for bonding sunglass lenses prepared from the composition according to any one of claims 3 to 9.